Usefulness of antimicrobial susceptibility in the eradication of Helicobacter pylori. (18th April 2012) - Cosme, A.; Montes, M.; Martos, M.; Gil, I.; Mendarte, U.; Salicio, Y.; Piñeiro, L.; Recasens, M. T.; Ibarra, B.; Sarasqueta, C.; Bujanda, L.
Abstract The rate of eradication of Helicobacter pylori with standard triple therapy using omeprazole, amoxicillin and clarithromycin (OAC) is unacceptable in populations with high rates of clarithromycin resistance (15–20%). The aim of this study was to compare the efficacy of 10‐day OAC therapy as the first‐line treatment in patients diagnosed by culture with antimicrobial susceptibility or diagnosed by a 13C‐labelled urea breath test (UBT) without antimicrobial susceptibility in an area where the clarithromycin resistance rate was 15–20%. This was a retrospective cohort study of 266 patients, recruited consecutively throughout 2008. A total of 247 H. pylori‐infected patients received antibiotic therapy (221 received the 10‐day OAC therapy and 26 received other regimens) of which 134 patients were diagnosed by culture of gastric samples followed by antimicrobial susceptibility testing and 113 were diagnosed by UBT. In all patients, the eradication of H. pylori was checked by UBT. The cost of eradication by 10‐day OAC treatment was assessed in each patient. The success rate of 10‐day OAC therapy in patients diagnosed by culture and by UBT was 88% (103/117) and 49% (51/104), respectively (p <0.0005). The treatment was also more cost‐effective in the former of these two groups (€571 versus €666). To perform culture and antimicrobial susceptibility of the H. pylori isolates was a more successful and cost effective strategy than empirical 10‐day OAC treatment in populations with high rates of resistance to clarithromycin.